A new genus of Barleeidae Gray, 1857 (Mollusca, Gastropoda) and the first occurrence of the genus Pseudodiala Ponder, 1967 off the Brazilian coast - Santos, Franklin Noel Dos; Absalão, Ricardo Silva (Zootaxa, 2006)
Ketosia new genus, Barleeidae, is described from off the Brazilian coast, based on conchological analysis of specimens collected through the REVIZEE Program and others from oil prospecting, off the coast of Rio de Janeiro State (24 o W). The new genus is characterised by: anteriorly convex to slightly convex shell profile; protoconch paucispiral, dome-shaped, its surface covered with irregular pits; and teleoconch smooth but with minute deep pits. The aperture is oval, and may be separated from the peripheral region of the teleoconch by a depression. Two new species belonging to this new genus are described herein. We also record, for the first time, the occurrence of the genus Pseudodiala Ponder, 1967 from the Brazilian coast, describing a new species.